Neuroprotective Effects of Curcumin against Oxygen-Glucose Deprivation/Reoxygenation-Induced Injury in Cultured Primary Rat Astrocyte by Improving Mitochondrial Function and Regulating the ERK Signaling Pathway. (12th July 2022) - Chen, Haojie; Tang, Guoke; Yu, Jiangming; Yu, Ronghua
Abstract : Objectives . Curcumin (Cur) is a natural polyphenol isolated from turmeric and has potent anti-inflammatory and antioxidant activities. This study aimed to explore the effects and possible mechanisms of curcumin on oxygen-glucose deprivation/reoxygenation (OGD/R)-induced injury in cultured rat astrocyte primary cells. Methods . After screening for effective doses, the cultured rat astrocyte primary cells were divided into three groups: control, OGD/R, and OGD/R + curcumin (10  μ M, 20  μ M, and 40  μ M). Cell viability was detected using CCK8 assays. The level of malondialdehyde and superoxide dismutase activity was determined using commercial kits. The endothelial nitric oxide synthase and adenosine triphosphate concentrations were determined by enzyme-linked immunosorbent assay. The mRNA levels of the inflammatory indexes interleukin (IL)-6, tumor necrosis factor (TNF)-alpha, and interleukin (IL)-1 β were evaluated by quantitative reverse-transcription polymerase chain reaction. Annexin V-fluorescein isothiocyanate/propidium iodide was used to detect apoptosis. JC-1 was used to assess the mitochondrial membrane potential. The protein expression of apoptosis-related proteins (B-cell lymphoma-2 (Bcl-2), BCL-2-associated X (Bax), and cleaved caspase 3), mitochondria-related proteins (dynamin-related protein 1 (DRP1), phosphorylated DRP1 (p-DRP1), and mitofusin 2), and essential proteins of the extracellular signal-regulated kinase (ERK) signaling pathway (ERK1/2, p-ERK1/2) were analyzed by western blot. Results . Our data indicated that curcumin reversed OGD/R-induced cell viability loss, oxidative stress, inflammatory cytokine production, and cell apoptosis in a dose-dependent manner. Furthermore, curcumin attenuated OGD/R-induced mitochondrial dysfunction and ERK1/2 phosphorylation in a dose-dependent manner. Conclusions . Curcumin protected against OGD/R-induced injury in rat astrocyte primary cells through improving mitochondrial function and regulating the ERK signaling pathway.